The myth of the high-efficiency external-combustion Stirling engine - Riley, Paul Howard (Scientific Research Publishing, 2015)
The reported discrepancy between theory and experiment for external combustion Stirling engines is explained by the addition of thermal resistance of the combustion gasses to the standard Carnot model. In these cases, the Stirling engine ideal efficiency is not as is normally reported equal to the Carnot cycle efficiency but is significantly lower. A new equation for ideal Stirling engine efficiency when the heat is obtained through external combustion without pre-heating the air, is presented and results for various fuels tabulated. The results show that petrol and diesel, internal combustion engines (Otto cycle) have a higher ideal efficiency than the Stirling engine. When comparing thermoacoustic engines heated by wood, efficiency should not be quoted as a percentage of the Carnot efficiency, but against a figure 48% lower than Carnot. The effect is not seen with electrically heated rigs, solar or nuclear fission heated engines.